Social-ecological drivers and dynamics of seagrass gleaning fisheries - Furkon; Natsir Nessa; Rohani Ambo-Rappe; Leanne Claire Cullen-Unsworth; Richard Kazimierz Frank Unsworth (Ambio, 2020)
Invertebrate gleaning (walking) fisheries are common within intertidal seagrass meadows globally, contributing to the food supply of hundreds of millions of people, but understanding of these fisheries and their ecological drivers are extremely limited. The present study provides a unique analysis of these fisheries using a combined social and ecological approach. Catches contained 34 species and were dominated by Bivalves, Urchins and Gastropods. CPUE in all sites varied from 0.05 to 3 kg gleaner −1 hr −1 , respectively, with the majority of fishers being women and children. Landings were of major significance for local food supply and livelihoods at all sites. Local ecological knowledge suggests seagrass meadows are declining in line with other regional trends. Increasing seagrass density significantly and positively correlated with CPUE of the invertebrate gleaning ( r = 0.830) highlighting the importance of conserving these threatened habitats. Understanding the complexities of these fisheries, their supporting habitats and their sustainability is important for the support of sustainable coastal livelihoods.